2021
DOI: 10.1111/ijcp.14506
|View full text |Cite
|
Sign up to set email alerts
|

Coronary revascularisation in patients with chronic kidney disease and end‐stage renal disease: A meta‐analysis

Abstract: Objectives To compare coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) for revascularising coronary arteries in patients with chronic kidney disease (CKD) and end‐stage renal disease (ESRD). CKD is described as a continuous decrease in the glomerular filtration rate or abnormalities in kidney structure or function. Methods PubMed, Cochrane Library and Embase databases were searched for studies on the revascularisation of coronary arteries in patients with CKD and ESRD. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
(128 reference statements)
1
7
0
1
Order By: Relevance
“…Several studies have investigated cardiovascular outcomes after PCI or CABG in patients with CKD. While CABG was reported to be associated with a higher risk of short-term mortality and stroke, MI and repeat revascularization were less frequent than in those who had undergone PCI in the long-term follow-up ( 3 , 4 , 13 , 14 ). The majority of these studies designated MACCE as the primary outcome and concluded CABG is associated with fewer adverse events in patients with CKD than in PCI ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies have investigated cardiovascular outcomes after PCI or CABG in patients with CKD. While CABG was reported to be associated with a higher risk of short-term mortality and stroke, MI and repeat revascularization were less frequent than in those who had undergone PCI in the long-term follow-up ( 3 , 4 , 13 , 14 ). The majority of these studies designated MACCE as the primary outcome and concluded CABG is associated with fewer adverse events in patients with CKD than in PCI ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 98%
“…mortality and stroke, MI and repeat revascularization were less frequent than in those who had undergone PCI in the long-term follow-up (3,4,13,14). The majority of these studies designated MACCE as the primary outcome and concluded CABG is associated with fewer adverse events in patients with CKD than in PCI (14,15).…”
Section: Cardiovascular Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Some patients with CKD will progress to kidney failure, which is the irreversible decline of kidney function, resulting in the accumulation of water, electrolytes, and metabolic waste in the body. [ 2 ] With CKD developing into kidney failure, there are 2 main treatments to maintain life, kidney transplantation and kidney replacement therapy. However, due to the limited number of transplantable organs, kidney replacement therapy has become the only option for most patients with kidney failure, [ 3 ] which has become a serious public health problem, not only because of the dramatic increase in the therapeutic cost but also because of the substantial economic burden and heavy social pressure on individuals, families, and the country.…”
Section: Introductionmentioning
confidence: 99%
“…Revascularization strategies are valuable options for these patients. However, previous studies have focused on CKD and ESRD patients [ 5 , 6 ]. On the other hand, only some studies have been conducted on KTRs, with no cumulative evidence regarding the most effective revascularization strategy [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%